Actively Simulated Floating Lossless Inductor for Short Range Wireless Communication - Pitchayanin Moonmuang; Tattaya Pukkalanun; Sumalee Unhavanich; Worapong Tangsrirat (My University, 2020)
This communication describes the resistorless simulation of the floating lossless inductor using three voltage differencing buffered amplifiers (VDBAs) and one grounded capacitor. The circuit employs only a grounded capacitor, and no other extra resistor element is employed. Thus, it is suitable for further communication integrated front-end circuit design in short-range wireless and application. The realized equivalent inductance value of the simulated inductor can be changed electronically via the external biasing currents of the VDBAs. Sufficient simulation results with the PSPICE program are provided to validate the functionality of the realized inductor. In addition to establishing the practical operation of the simulator, the measured test results obtained from hardware implementation using readily available integrated chips (ICs) are also included.
Keywords: Biasing; Radio Frequency Integrated Circuit Design